Combination drug therapy prevents CIAKI by suppressing ER stress-induced apoptosis - Xuan Wang; Shan Han; Lili Zhao; Hongliang Cong (Scientific Reports)
Abstract Contrast-induced acute kidney injury (CIAKI) is an important clinical complication that occurs after the application of contrast agent in percutaneous coronary intervention. The pathogenesis of CIAKI is complex. Studies have shown that cell apoptosis induced by endoplasmic reticulum stress (ERS) plays an important role in renal tubular injury in CIAKI. These findings suggest that atorvastatin, probucol and alprostadil can inhibit renal tubular cell apoptosis to prevent CIAKI. However, there is no specific research on the above effects of drug combinations. Therefore, this study aimed to establish a rat CIAKI model with meglumine diatrizoate and add drug intervention to compare the influence of combined drugs with that of atorvastatin alone on CIAKI via the inhibition of ERS-specific molecular chaperones. Fifty Wistar rats were randomly divided into 5 groups: Group A + CC (atorvastatin group, n = 10); Group PA + CC (probucol + atorvastatin group, n = 10); Group AA + CC (alprostadil + atorvastatin group, n = 10); Group PCC (contrast group, n = 10); and Group NCC (control group, n = 10). Among the five groups, Group PCC presented the significantly highest creatinine increase rate and protein and nucleic acid expression levels, with the most severe cell injury and apoptosis observed via HE and TUNEL staining. Compared with those in the atorvastatin group, the rate of increase in creatinine and protein expression in the combined treatment groups were decreased to some extent, and the histological morphology was also improved. This was especially evident in Group AA + CC. Renal cell apoptosis induced by the ERS pathway may play an important role in the pathogenesis of CIAKI induced by meglumine diatrizoate. Atorvastatin, probucol and alprostadil can prevent the occurrence of CIAKI, and the ERS-induced apoptosis pathway is involved in this mechanism. The protective effect of probucol or alprostadil combined with atorvastatin on CIAKI may be stronger than that of atorvastatin alone, with a greater effect of the combination of alprostadil and atorvastatin.